Crystal structure of (Z)-2-(1-bromo-2-phenylvinyl)-5-ethyl-2-methyl-1,3-dioxane-5-carboxylic acid, C15H17Br1O4 - Jia Guo-Kai; Yuan Xian-You (Zeitschrift für Kristallographie - New Crystal Structures)
C15H17Br1O4, monoclinic, P21/n (no. 14), a = 7.1178(16) Å, b = 8.752(2) Å, c = 24.554(6) Å, β = 94.761(3)°, V = 1524.3(6) Å3, Z = 4, Rgt(F) = 0.0275, wRref(F2) = 0.0694, T = 296(2) K.